Disposition of enrofloxacin administered intrauterine in buffaloes with endometritis - PAWAR, A H; SOMKUWAR, A P; PAWAR, S D; SHINDE, V S; RANADE, V V (The Indian Journal of Animal Reproduction, 2003)
The present study was aimed at estimating extent of enrofloxacin absorption across the uterus after its intrauterine administration. Enrofloxacin (3 mg/kg B.wt.) was administered (I/U) to six buffaloes with history of endometritis and blood samples before and 1,2,3,4 and 5 hours after administration were collected. The enrofloxacin levels were detected by employing microbiological assay technique, using Bacillus subtilis ATCC-6633 as test organisms. Disposition studies showed that detectable levels (0.08 mcg/ ml) of enrofloxacin in blood were achieved one hour after intrauterine administration and persisted upto 4 hours. Therapeutically effective levels were achieved upto 2 to 3 hrs. It was concluded that therapeutically effective enrofloxacin levels could not be achieved in blood and uterine tissues after intrauterine infusion with enrofloxacin 1500 mg.